2018
DOI: 10.4103/ejd.ejd_380_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative abrasive wear resistance and surface analysis of dental resin-based materials

Abstract: Objective:The objective of this study was to assess the surface properties (microhardness and wear resistance) of various composites and compomer materials. In addition, the methodologies used for assessing wear resistance were compared.Materials and Methods:This study was conducted using restorative material (Filtek Z250, Filtek Z350, QuiXfil, SureFil SDR, and Dyract XP) to assess wear resistance. A custom-made toothbrush simulator was employed for wear testing. Before and after wear resistance, structural, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
1
31
0
5
Order By: Relevance
“…The solubility values were also under the accepted values, ranging from 0.14 µm/cm 3 to 2.40 µm/cm 3 . 3,21 The limitations of the present study are related to the difficulty in simulating oral conditions. The in vitro setup simulates extreme conditions, such as immersion of samples for 7 consecutive days in coffee.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The solubility values were also under the accepted values, ranging from 0.14 µm/cm 3 to 2.40 µm/cm 3 . 3,21 The limitations of the present study are related to the difficulty in simulating oral conditions. The in vitro setup simulates extreme conditions, such as immersion of samples for 7 consecutive days in coffee.…”
Section: Discussionmentioning
confidence: 94%
“…It is common for the clinician to worry about how these materials behave in different situations. 9 However, in the study by Nayyer et al (2018), 21 in which the hardness of resinous compounds was evaluated after simulated brushing cycles, the authors concluded that brushing was not able to compromise the hardness of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 55 ] testing wear and microhardness found that bulk-fill resin materials have comparable microhardness to conventional ones and present minimal change in surface roughness upon wear. This in turn could decrease bacterial adhesion to the surface of the restoration.…”
Section: Discussionmentioning
confidence: 99%
“…The worn, rough surface encourage plaque accumulation and attrition with the opposing tooth. Matrix structure and fillers type and size determine the wear resistance of restorative materials [10,11]. Zafar et al [12] reported that wear increases the surface hardness and elastic moduli of metallic restorations.…”
Section: Introductionmentioning
confidence: 99%